Securing Agricultural Land Investment Contract: Resolving Salient Agricultural Land Dispute in Indonesia - Antarin Prasanthi Sigit; Daryono Daryono (Universitas Pelita Harapan, 2021)
In 2014, Indonesia introduced a more progressive law to ease foreign investment in plantations. This policy seems to resuscitate the legacy of the plantation during colonial times as a source of state revenue. This law however has not signified the increases in plantation companies. One of the major causes has been an inadequate quality of contracts such as lack of transparency, participation, and coherence. In practice, the plantation contract still utilizes the outdated uniform contract based on the 18th century Civil Code adopted from the Dutch Civil Code. These have challenged certainty and enforceability. In line with the liberation of plantations in developing nations, the International Institute for Unification of Private law (UNIDORIT) is drafting the universal guideline for a responsible agricultural land investment contract. The guideline aims at providing the model of a responsible agricultural land investment contract. The model contract considers a broad range of social, political, economic, and cultural aspects to ensure that stakeholders' interests are respected while it also needs to adhere to global issues, such as food security, poverty elevation, and environmental preservation. The article is part of a study attempting to explore the deficiencies of the existing plantation contract and to seek the potential adoption of the UNIDROIT guideline in Indonesia. There are multi-facet challenges to adopt the UNIDROIT guideline as the stakeholders and legal counsel capacity are still limited. Those result in complexity during the agricultural land dispute settlement process in which non-legal factors contribute to its success. This article explores to map the potential issues and to propose a model of more effective agricultural land dispute settlement.